Sources of ammonium in seasonal wet deposition at a coastal New England city. (1st September 2021) - Le Roy, Emmie; Walters, Wendell W.; Joyce, Emily E.; Hastings, Meredith G.
Abstract: National monitoring networks have reported an increase in ammonium (NH4 + ) deposition, such that NH4 + now dominates inorganic nitrogen deposition across most of the United States. Atmospheric deposition of fixed nitrogen has significant environmental consequences, including acidification and eutrophication. Thus, understanding source contributions is critical for formulating policies to mitigate the effects of excess nitrogen in sensitive ecosystems. Here, we investigated sources of wet-deposited NH4 + (w-NH4 + ) in Providence, RI, U.S.A., a mid-sized coastal city at the head of Narragansett Bay. We utilized concentration measurements, nitrogen stable isotopes (δ 15 N), and air mass back trajectory analysis for precipitation events and intra-event samples collected between January–November 2018. There was a general lack of seasonality in δ 15 N(w-NH4 + ). Air mass origin had a strong influence on [w-NH4 + ], but [w-NH4 + ] was not related to δ 15 N(w-NH4 + ), suggesting the potential dominance of a single NH3 emission source type. An average δ 15 N(w-NH4 + ) of −3.7 ± 3.5‰ ( n  = 42) was measured for daily-based precipitation. This value is consistent with previous measurements in the U.S. over the past 40 years, indicating a similar source of NH3 across the U.S. likely derived from agricultural activities. Intra-event analysis from precipitation events collected throughout the year found frequent mid- and end-event [w-NH4 + ] peaks that were suggested to be related to in-cloud [w-NH4 + ] changes rather than changes in below-cloud scavenging due to a consistent corresponding shift in precipitation intensity. Large intra-event δ 15 N(w-NH4 + ) variations as high as 15.9‰ were also observed. However, the cumulative mass-weighted δ 15 N(w-NH4 + ) of the intra-event series tended to converge to a similar value (−4.8 ± 1.3‰; n  = 6). Overall, our results indicate that long-range transport via in-cloud scavenging tended to play a stronger role in shaping w-NH4 + patterns compared to local emissions at our study site. Highlights: Similar seasonal δ 15 N(w-NH4 + ) values suggest one dominant NH3 emission source type. Intra-event sampling indicates in-cloud scavenging strongly influences δ 15 N(w-NH4 + ). Long-range transport of NH4 + contributes to wet deposited N at a coastal urban site. Transport of distant, agricultural NH3 may be significant in urban N budgets.